2007
DOI: 10.1016/j.jacc.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of T-Wave Alternans in Patients With Heart Failure Due to Nonischemic Cardiomyopathy

Abstract: Among NYHA functional class II/III nonischemic cardiomyopathy patients, an abnormal TWA test is associated with a 4-fold higher risk of cardiac death and life-threatening arrhythmias. Patients with normal TWA tests have a very good prognosis and are likely to benefit little from ICD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 41 publications
1
80
2
4
Order By: Relevance
“…Although MTWA has been promoted as a predictor of ventricular events, its value is controversial because prospective trial results have been inconsistent [32][33][34] and the optimal population in which it can be used for risk stratification is yet to be determined.…”
Section: Microvolt T-wave Alternansmentioning
confidence: 99%
“…Although MTWA has been promoted as a predictor of ventricular events, its value is controversial because prospective trial results have been inconsistent [32][33][34] and the optimal population in which it can be used for risk stratification is yet to be determined.…”
Section: Microvolt T-wave Alternansmentioning
confidence: 99%
“…A test that did not satisfy positive or negative criteria was classified as indeterminate. On the basis of previously published studies, we further classified results as "abnormal" (for positive and indeterminate test results) or "negative" (negative result) (22). If initially an indeterminate result was obtained, immediate retesting was attempted.…”
Section: Mtwa Testing Protocolmentioning
confidence: 99%
“…Approximately one-third of the symptomatic patients with LVEF ≤ 0.35 may test MTWA negative 7,12 . However, a non-negative test in the remaining patients may serve as a specific call to action for the patient and referring Stecker et al 31 found that LVEF had been measured in only 17% of 714 cases of SCD.…”
Section: Mtwa As a Guide To Icd Therapymentioning
confidence: 99%
“…Many studies conducted in patients without implanted ICDs have found MTWA to be a highly accurate risk stratifier and, in particular, have found that the rate of ventricular tachyarrhythmic events (VTEs) among patients who test MTWA negative is exceedingly low [1][2][3][4][5][6][7] suggesting that ICD therapy may not benefit such patients 8 . As a result, MTWA has been proposed as a means of guiding implantable cardioverter defibrillator (ICD) therapy in patients with risk factors for SCD but without a prior history of sustained VTEs (primary prevention patients).…”
Section: Introductionmentioning
confidence: 99%